2013
DOI: 10.1142/s0129065714500051
|View full text |Cite
|
Sign up to set email alerts
|

Drug Polyconsumption Is Associated With Increased Synchronization of Brain Electrical-Activity at Rest and in a Counting Task

Abstract: Drug abusers typically consume not just one but several types of drugs, starting from alcohol and marijuana consumption, and then dramatically lapsing into addiction to harder drugs, such as cocaine, heroin, or amphetamine. The brain of drug abusers presents various structural and neurophysiological abnormalities, some of which may predate drug consumption onset. However, how these changes translate into modifications in functional brain connectivity is still poorly understood. To characterize functional conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 65 publications
3
24
0
Order By: Relevance
“…Most of the causal interactions between abnormal regions were remote pathways, so it could also be explained by previous studies that the remote connectivity decreased in heroin addicts [16,45]. Additionally, by counting the outflows and inflows of each source region, we found parietal and left occipital regions were the two dominant hubs related with the BFS alterations induced by heroin addiction; these findings were supported by [17] and [55], which revealed the parietal and left occipital regions had abnormal activities related with HA subjects. Since this work specially focused on the exploring of BFS alterations of heroin addicts, there were several limitations to be improved in the future work.…”
Section: Abnormal Effective Connectivitysupporting
confidence: 82%
See 1 more Smart Citation
“…Most of the causal interactions between abnormal regions were remote pathways, so it could also be explained by previous studies that the remote connectivity decreased in heroin addicts [16,45]. Additionally, by counting the outflows and inflows of each source region, we found parietal and left occipital regions were the two dominant hubs related with the BFS alterations induced by heroin addiction; these findings were supported by [17] and [55], which revealed the parietal and left occipital regions had abnormal activities related with HA subjects. Since this work specially focused on the exploring of BFS alterations of heroin addicts, there were several limitations to be improved in the future work.…”
Section: Abnormal Effective Connectivitysupporting
confidence: 82%
“…Subjects remain at rest instead of performing cognitive tasks, making it more readily applicable to study the inner BFS alterations induced by mental disorders [5]. From EEG recording under the resting state with eyes closed, Franken et al found heroinrelated thoughts and craving were associated with temporal interhemispheric beta2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and delta (1-4 Hz) coherence, frontal interhemispheric alpha1 (8-10 Hz) coherence, and increased gamma activities [3]; Fingelkurts et al found brain functional networks in alpha and beta bands were indeed significantly disrupted by chronic opioid abuse [16]; drug abusers had higher synchronization levels between frontal and posterior cortical regions in θ (4-8 Hz) band [17].…”
mentioning
confidence: 99%
“…They then used this region as a seed for the resting state fMRI functional connectivity analysis. Coullaut-Valera et al [68] used electroencephalography (EEG) to investigate impaired functional connectivity in polydrug users. EEG has low spatial resolution and high temporal resolution and so it is natural to combine it with fMRI which has a high spatial resolution, but relatively low temporal resolution, to gain more understanding of brain connectivity.…”
Section: Five Year Viewmentioning
confidence: 99%
“…The hypothesis that S-W disturbances in AUD may be caused by the neuroadaptation at the level of CCC-PPT (hypersensitivity of kainite and NMDA receptors) is also supported by the findings that gamma band activity increases in AUD [102, 103]. For example, all cells in the CCC-PPT are geared to fire at gamma band frequencies and the generation of this activity involves voltage-dependent high threshold N- and P/Q-type calcium channels [reviewed in 211214].…”
Section: Possible Mechanisms Of Alcohol’s Action In Producing Sleementioning
confidence: 88%